Associations of minerals intake with colorectal cancer risk in the prostate, lung, colorectal, ovarian cancer screening trial - Li, Siyue; Ren, Qingqian; Song, Zixuan; Liu, Baixue; Wang, Dan; Shang, Yanna; Wang, Hao (Frontiers in Nutrition, 2024)
Abstract Objective: Exploring the association between common mineral intake and the risk of colorectal cancer (CRC). Methods: We utilized the multivariate Cox proportional hazards model to assess the association between intake of minerals and the risk of CRC, estimating hazard ratios (HRs) and 95% confidence intervals (CIs). Results: A total of 101,686 eligible participants were included in the analysis of this study, including 1,100 CRC cases. After adjusting for potential confounders, we found that total zinc intake (HRQ4vs.Q1: 0.79, 95%CI 0.67-0.93; P for trend < 0.05), iron intake (HRQ4vs.Q1: 0.81, 95%CI 0.68-0.96; P for trend < 0.05), copper intake (HRQ4vs.Q1: 0.80, 95%CI 0.68-0.95; P for trend < 0.05), selenium intake (HRQ4vs.Q1: 0.83, 95%CI 0.69-0.98; P for trend < 0.05) were significantly negatively associated with the incidence of CRC, but magnesium intake in the appropriate range is associated with a reduced risk of CRC (HRQ3vs.Q1: 0.77, 95%CI 0.65-0.91; P for trend > 0.05). Conclusions: Our findings suggested that an appropriate intake of total zinc, iron, copper, selenium and magnesium were associated with lower CRC risk.